Long-term organic fertilizer additions elevate soil extracellular enzyme activities and tobacco quality in a tobacco-maize rotation - Yonglei Jiang; Ruqiang Zhang; Cuiping Zhang; Jiaen Su; Wen-Feng Cong; Xiaopeng Deng (Frontiers in Plant Science, 2022)
Organic fertilizer is effective in improving soil quality, and promoting crop growth. Combined organic and inorganic fertilization has been proved as a more favorable way to tobacco yield and quality. However, the mechanisms underlying tobacco yield and quality under combinations of different organic and inorganic fertilizer remain unclear. We conducted a 12-year tobacco (Nicotiana tabacum L.)-maize crop rotation field experiment in Yanhe experimental station, China to examine the yields and qualities of tobacco, soil nutrients, and extracellular enzyme activities associated with carbon, nitrogen, and phosphorus cycles in response to different fertilization treatments. Five fertilization treatments (no fertilization; 75 kg N fertilizer ha–1; 450 kg oil cake ha–1 + 75 kg N fertilizer ha–1; 15,000 kg pig dung ha–1 + 60 kg N fertilizer ha–1; 3,000 kg straw ha–1 + 75 kg N fertilizer ha–1) were applied to tobacco while maize was fertilized with inorganic compound fertilizers. After 12 years of tobacco-maize rotation, the results showed that organic fertilizer additions elevate tobacco yield and quality, and the soil extracellular enzymes activities. Gram-negative bacteria, actinomycetes, and total soil microbial biomass were increased by organic fertilizer additions, both plant-based (oil cake and straw) and animal-based (pig dung) organics. The levels of soil organic matter, total organic carbon, total phosphorus and available phosphorus are higher in pig dung addition treatment than oil cake and straw additions. By variance analysis with respect to fertilization treatments, organic sources differentially affected the activities of diverse soil enzymes. The redundancy analysis gave that yield and quality of tobacco leaves (upper, middle, and lower leaves) positively related to soil extracellular enzyme activities. Based on analysis of yield and quality of tobacco leaves with extracellular enzyme activities and soil nutrients, it is suggested animal-based organic fertilizer, thus pig dung, should be used in combining with chemical fertilizers to improve the quality of tobacco and soil nutrients.